2013
DOI: 10.1111/ijfs.12078
|View full text |Cite
|
Sign up to set email alerts
|

Alginate‐based and protein‐based materials for probiotics encapsulation: a review

Abstract: Owing to their considerable beneficial effects on human health, probiotics have been increasingly incorporated into food products. However, many findings have demonstrated that their survival and stability are very sensitive to processing and host gastrointestinal tract. To solve these problems, encapsulation techniques have been received considerable attention these days. So, in this review paper, methods for probiotics encapsulation, alginate-based and protein-based materials for probiotics encapsulation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
97
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 111 publications
2
97
0
1
Order By: Relevance
“…Probiotics are defined as "live microorganisms which, when administered in adequate amounts, confer a health benefit on the host" (Sohail et al 2012;Dong et al 2013;Pan et al 2013;Shi et al 2013a). It can provide various health benefits, including preventing diarrhoea, balancing intestinal microflora, stimulating the immune system, improving lactose intolerance, etc.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Probiotics are defined as "live microorganisms which, when administered in adequate amounts, confer a health benefit on the host" (Sohail et al 2012;Dong et al 2013;Pan et al 2013;Shi et al 2013a). It can provide various health benefits, including preventing diarrhoea, balancing intestinal microflora, stimulating the immune system, improving lactose intolerance, etc.…”
Section: Introductionmentioning
confidence: 99%
“…It can provide various health benefits, including preventing diarrhoea, balancing intestinal microflora, stimulating the immune system, improving lactose intolerance, etc. (Rajam et al 2012;Dong et al 2013;Khan et al 2013;Pan et al 2013;Shi et al 2013a, b;Chen et al 2014). However, it has been reported that many factors, such as low pH, hydrogen peroxide, dissolved oxygen, and storage temperature can affect the viability of probiotics (Champagne et al 2011;Rajam et al 2012;Dong et al 2013;Chen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations